Distant Reading the Body, 1640–1699. (14th January 2019) - Mann, Rachel; Gavin, Michael
Abstract: This paper analyses seventeenth-century discourse of the human body over the Early English Books Online full-text corpus. Anatomy and medicine depict the body as a physiological object, knowable mainly through its parts and processes. Fiction and poetry tend to represent the body as a social entity, knowable primarily through intersubjective action and ethical ideals. In both contexts, bodies are perceived and described through close attention to their parts, but when bodies are conceived as such, they are described as abstract entities that organize the whole. This distinction is difficult to see at the level of close reading but unmistakable at larger scale. Deep conceptual structures at work underneath both anatomy and fiction, we argue, underlie a conception of the body that informs more particularized notions of mobility, sociality, and physicality.